Reorienting India's financial system: In conversation with Dr Duvvuri Subbarao, Governor, Reserve Bank of India - Vivek Moorthy (IIMB Management Review, 2012)
Confronted by a slowing economy, the Reserve Bank of India has undertaken steps to revive it. These measures, however, run the risk of worsening current high levels of inflation. This paper examines certain aspects of India's financial system that have contributed to this situation. It argues that unduly low yields on Government bonds have prevented a healthy financial system from developing, with adverse impact upon inflation and other macroeconomic outcomes. It suggests that India should focus far more on domestic, and less on external, financial liberalisation. Specifically, yields on non-market borrowing, such as Provident Fund deposits, should be benchmarked to a low frequency measure of consumer price inflation.